2010
DOI: 10.1111/j.1600-0463.2010.02604.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Foxp3‐, CD4‐ and CD8‐positive lymphocytic cells in benign and malignant prostate tissue

Abstract: Foxp3 is a transcription factor that inhibits antitumor immune response and is expressed in regulatory T cells (Tregs). High levels of Tregs have been reported in several human cancers. This study investigates the distribution of cells positive for Foxp3, CD4 and CD8 in benign prostatic tissues and prostatic carcinoma. Tissue microarrays were constructed from radical prostatectomy specimens of 36 patients. From each patient, six cores were taken: two cores from cancer, one from benign tissue of each of the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
(29 reference statements)
4
25
1
5
Order By: Relevance
“…7,10,24 In line with previous reports, 12,14,34 our study revealed a high degree of infiltration of both T helper cells as determined by CD4 expression and T cytotoxic cells as determined by CD8 expression. The present study also demonstrates that IHC markers of inflammation are positively related to histopathological classification of inflammation, as all of the three T-cell subtypes were positively associated with the presence of moderate/severe chronic inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…7,10,24 In line with previous reports, 12,14,34 our study revealed a high degree of infiltration of both T helper cells as determined by CD4 expression and T cytotoxic cells as determined by CD8 expression. The present study also demonstrates that IHC markers of inflammation are positively related to histopathological classification of inflammation, as all of the three T-cell subtypes were positively associated with the presence of moderate/severe chronic inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported increased levels of regulatory T cells in patients with prostate cancer, 29 with cells expressing Fox-P3 linked to acquired treatment resistance. 30 In our study, no association was seen with concomitant diseases or treatments; specifically steroid use at the time of blood sampling for expression analyses was not associated with the LPD1 profile and the different LPD groups. Ross and colleagues 31 have also described a prognostic signature for patients with castration-resistant prostate cancer using whole-blood RNA and qRT-PCR analyses of 168 preselected genes that associate with altered cellular and humoral immunity focusing on the monocyte and macrophage lineage.…”
Section: Discussioncontrasting
confidence: 64%
“…53 Tregs are rarely seen in enucleated choroidal melanoma, 54 however they are found in human prostate cancer and are more common in the peripheral and transition zones than in the core of the tumor. 55 In gliomas, infiltration of Tregs was correlated with heme oxygenase-1 (HO-1) mRNA 56 and progression of the disease. Increased populations of Tregs have been found in hepatocellular carcinoma, and even in nontumorous liver that contains primary hepatic tumors.…”
Section: Cd4+cd25+foxp3+ Regulatory T Cellsmentioning
confidence: 99%